Cis- and trans-acting influences on telomeric position effect in Drosophila melanogaster detected with a subterminal transgene. - Mason, J.M.; Konev, A.Y.; Golubovsky, M.D.; Biessmann, H. (Genetics, 2003)
One model of telomeric position effect (TPE) in Drosophila melanogaster proposes that reporter genes in the vicinity of telomeres are repressed by subterminal telomere-associated sequences (TAS) and that variegation of these genes is the result of competition between the repressive effects of TAS and the stimulating effects of promoters in the terminal HeT-A transposon array. The data presented here support this model, but also suggest that TPE is more complex. Activity of a telomeric white reporter gene increases in response to deletion of some or all of the TAS on the homolog. Only transgenes next to fairly long HeT-A arrays respond to this trans-interaction. HeT-A arrays of 6-18 kb respond by increasing the number of dark spots on the eye, while longer arrays increase the background eye color or increase the number of spots sufficiently to cause them to merge. Thus, expression of a subtelomeric reporter gene is influenced by the telomere structure in cis and trans. We propose that the forces involved in telomere length regulation in Drosophila are the underlying forces that manifest themselves as TPE. In the wild-type telomere TAS may play an important role in controlling telomere elongation by repressing HeT-A promoter activity. Modulation of this repression by the homolog may thus regulate telomere elongation.